YTHDC1 Regulates the Migration, Invasion, Proliferation, and Apoptosis of Rheumatoid Fibroblast-Like Synoviocytes - Feng, Zhi-wei; Yang, Chen-fei; Xiao, He-fang; Yuan, Fa; Chen, Feng; Zhang, Bo; Zhang, Jun; Tan, Min; Guo, Ming-gang (Frontiers in Immunology, 2024)
Rheumatoid arthritis (RA), a chronic autoimmune condition, is characterized by persistent synovial inflammation, bone degradation, and progressive joint deterioration. Despite considerable research efforts, the precise molecular mechanism underlying RA remains elusive. This investigation aims to elucidate the potential role and molecular mechanism of N6-methyladenosine (m 6 A) methylation regulators in the pathogenesis of RA.In this study, we employed bioinformatics tools to elucidate the association between RA and m 6 A modifications, aiming to identify potential biological markers. We extracted datasets GSE12021, GSE55235, and GSE55457 from the Gene Expression Omnibus (GEO) database for comprehensive analysis. Utilizing differential expression analysis, protein-protein interaction (PPI) analysis, and single-cell sequencing techniques, we identified pivotal hub genes implicated in the pathogenesis of RA.Subsequently, we assessed the correlation between these hub genes and the pathogenesis of RA using Gene Set Enrichment Analysis (GSEA). Both in vivo and in vitro experiments were performed to confirm the expression and functional roles of the identified key hub gene in RA.Differential expression analysis, PPI analysis, and single-cell analysis identified three key hub genes (YTHDC1, YTHDC2, and YTHDF2) associated with RA. GSEA results further revealed that these genes are enriched in pathways associated with inflammatory responses. Subsequent correlation analysis demonstrated a significant negative correlation between YTHDC1 expression and CD8+ T cell levels. Notably, the gene and protein expression levels of YTHDC1 and YTHDF2 were significantly reduced in the synovial tissue of RA patients. Furthermore, silencing YTHDC1 in fibroblast-like synoviocytes (FLSs) significantly inhibited their migration, invasion, proliferation, and induced apoptosis.YTHDC1 may potentially be involved in the pathogenesis of RA through its regulation of migration, invasion, proliferation, and apoptosis in FLSs.